Effects of dexmedetomidine and esmolol on systemic hemodynamics and exogenous lactate clearance in early experimental septic shock (2016)
Persistent hyperlactatemia during septic shock is multifactorial. Hypoperfusion-related anaerobic production and adrenergic-driven aerobic generation together with impaired lactate clearance have been implicated. An excessive adrenergic response could contribute to persistent hyperlactatemia and adrenergic modulation might be beneficial. We assessed the effects of dexmedetomidine and esmolol on hemodynamics, lactate generation, and exogenous lactate clearance during endotoxin-induced septic shock. Methods: Eighteen anesthetized and mechanically ventilated sheep were subjected to a multimodal hemodynamic/perfusion assessment including hepatic and portal vein catheterizations, total hepatic blood flow, and muscle microdialysis. After monitoring, all received a bolus and continuous infusion of endotoxin. After 1 h they were volume resuscitated, and then randomized to endotoxin-control, endotoxin-dexmedetomidine (sequential doses of 0.5 and 1.0 μg/k/h) or endotoxin-esmolol (titrated to decrease basal heart rate by 20 %) groups. Samples were taken at four time points, and exogenous lactate clearance using an intravenous administration of sodium L-lactate (1 mmol/kg) was performed at the end of the experiments